Haematobiochemical Profiles as Indicators of Trypanosoma evansi Infection in Cattle of Selected Agro Ecological Zones of Thrissur and Palakkad Districts of Central Kerala - P, Anandhabhairavi; K, Syamala; Lakshmanan, Bindu; R, Radhika; Rajagopal, Asha; Thomas, Marykutty; P S, Archana (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
The study investigated haemato-biochemical changes in Trypanosoma evansi infected cattle of Thrissur and Palakkad districts of central  Kerala, during a one-year timeframe. Blood samples were collected from 252 randomly selected, apparently healthy cattle exhibiting no  evident signs of anorexia or recumbency. Blood smear examination revealed flagellate organisms with central nucleus and an undulating  membrane. Confirmation was done using PCR targeting VSG gene which produced a 227 bp product. Complete blood count (CBC) was  performed using a three-part automated haematological analyzer on 10 healthy control animals, 24 animals infected with Trypanosoma  spp. alone and 47 animals that were co-infected with Anaplasma spp. and Theileria spp., which revealed highly significant differences in  the total erythrocyte count, haemoglobin, packed cell volume, mean corpuscular haemoglobin, mean corpuscular volume and mean  platelet volume. The serum biochemical values estimated in 10 healthy control animals along with 13 animals infected with Trypanosoma spp. alone and 12 animals with Theileria spp. and Anaplasma spp. showed a highly significant difference in the alkaline phosphatase,  albumin and indirect bilirubin in affected individuals. The cattle suffered from macrocytic hypochromic anaemia associated with T. evansi infection and had a significant clinical manifestation that results from multiple pathological mechanisms. The parasite's presence in the  bloodstream leads to haemolysis, immune-mediated destruction of erythrocytes, and impaired erythropoiesis, contributing to reduced  red blood cell count and haemoglobin levels. Regular monitoring and implementing effective vector control strategies are crucial in  managing T. evansi infections and preventing anaemia in affected cattle.
Keywords: Anaemia; Cattle; PCR; Serum biochemistry; Trypanosoma evansi